Cable-stayed cantilever structures as an expat of unique application in the construction of a building located in seismic area - an author`s project of multifunctional building in Lisbon, Portugal - Grębowski, Karol; Werdon, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski)
The article presents numerical simulations for the modelling of seismic impact on the structure of unique cantilever cablestayed structure with the application of two methods. The Response Spectrum method, in which a spectrum of the structure?s responses to an earthquake`s impact is generated, and the Accelerogram method, in which we generate dynamic load in the form of a diagram of the connection between acceleration and time for the actual readings during a real earthquake. Both methods have been presented for the El Centro earthquake spectrum.
Keywords: cantilever structures; seismic analysis; dynamic analysis; cable-stayed structures